Are Children Safe from Crime?: Focusing on Streets in Elementary School Zones. Issue 1 (1st January 2017) - Byun, Gidong; Ha, Mikyoung
Abstract : The objective of this study was to determine street environments wherein fear of crime and actual crime are highest in the environments surrounding elementary schools. To achieve this objective, elementary students′ fear of crime and actual crime experienced were analyzed. The study adopted a geographical method based on streets. The study results were as follows. First, a large number of elementary students experienced fear of crime on the road at the school they attended. Female students feared crime more than male students. Second, students′ fear of crime was mainly attributed to human factors (Many Bullies, Few People). Third, most elementary students experienced a fear of crime within a certain distance (500 m) from the school. Fourth, fear of crime and actual crime occurred mainly in small streets, small parks, or middle or high schools (advanced schools) nearby. Fifth, fear of crime and actual crime occurred near geographically similar elementary schools. Sixth, elementary students primarily experienced a fear of crime and actual crime on streets in densely populated residential areas.